Genomic insight into Aquimarina longa SW024T: its ultra-oligotrophic adapting mechanisms and biogeochemical functions. (December 2015) - Xu, Tingting; Yu, Min; Lin, Heyu; Zhang, Zenghu; Liu, Jiwen; Zhang, Xiao-Hua
Abstract Background South Pacific Gyre (SPG) is the largest and clearest gyre in the world, where the concentration of surface chlorophylla and primary production are extremely low.Aquimarina longa SW024T was isolated from surface water of the SPG center. To understand how this bacterium could survive in this ultra-oligotrophic oceanic environment and its function in biogeochemical cycle, we sequenced the genome ofA. longa SW024T and performed extensive genomic analyses. Methods Genomic DNA was extracted and sequenced using Illumina Hiseq 2000 and Miseq platform. Genome annotation, genomic comparison and phylogenetic analyses were performed with the use of multiple bioinformatics tools like: BLAST+ 2.2.24, Glimmer3.0, RAST server, Geneious 4.8.5, ClustalW2 and MEGA5. Physiological and morphological features were tested by bacterial culture, electron microscopy, fluorescence microscopy and exopolysaccharides extraction. Results Analysis of sevenAquimarina genomes and 30 other genomes ofFlavobacteriaceae isolated from seawater showed that most of the strains had low DNA G + C contents, andAquimarina had larger genomes than other strains. Genome comparison showed varying genomic properties among sevenAquimarina genomes, including genome sizes and gene contents, which may warrant their specific adaptive strategies. Genome ofA. longa SW024T was further compared with the genomes of two otherAquimarina species which were also isolated from the SPG andA. longa SW024T appeared to have much more genes related to replication, recombination and repair. As a copiotroph, A. longa SW024T is long in length, and possesses large genome size and diverse transporters. However, it has also evolved many properties to survive in the oligotrophic marine environment. This bacterium grew better on solid medium than in liquid medium, suggesting it may be liable to attach to particle surfaces in order to survive in the nutrient-limiting environment. Gliding motility and the capacity to degrade various polymers possibly allow the bacterium to grow on detritus particles and use polymeric substances as carbon and energy sources. Moreover, genes related to carbon, nitrogen, and sulfur metabolisms were identified, which showed thatA. longa SW024T might be involved in various elemental cycles. Conclusions Genomic comparison ofAquimarina genus exhibits comprehensive capabilities of the strains to adapt to diverse marine environments. The genomic characteristics ofA. longa SW024T reveal that it evolves various strategies to cope with both copiotrophic and ultra-oligotrophic marine environment, which provides a better understanding of the survival abilities of bacteria in prevalent and even extreme oceanic environments. Furthermore, carbon, nitrogen and sulfur utilization ofA. longa SW024T may represent its potential functions in the global biogeochemical cycle.